Luminescence of CeI3 in organic solvents and its application in water detection. (1st March 2021) - Wang, Chenyang; Liu, Xiyan; She, Changfeng; Li, Yangjuan
Graphical abstract: We demonstrate the potential application of commercial CeI3 for the detection of trace water in organic solvents on the basis of the solvoluminescence of CeI3 . Highlights: Commercial CeI3 is a convenient luminescent sensor for the detection of trace water in organic solvents. The detection limit for water in THF, CH3 CN and Et2 O is 0.1% (v/v). Trace water detection is based on the change in solvoluminescence. Solvated Ce(III) complexes are converted to hydrates upon water addition into organic solvents. Abstract: Molecular Ce(III) complexes are newly developed luminophores that have potential applications in a number of fields. However, there have been very limited studies regarding the application of solvoluminescent Ce(III) complexes. In this paper, we report the luminescence of CeI3 in different organic solvents. Violet or blue emissions were observed for CeI3 dissolved in THF, CH3 CN and Et2 O under ultraviolet irradiation. The luminescent properties are correlated with the structures of solvated complexes as exemplified in the CeI3 (THF)4 case. The solvoluminescence is strongly affected by the presence of water which converts solvated Ce(III) into cerium hydrates. The concentration of water lowered to 0.1 vol% was tested in THF, CH3 CN and Et2 O, indicating the potential application of commercial CeI3 as a convenient luminescent sensor for the detection of trace water in organic solvents.